2018
DOI: 10.1155/2018/3437417
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Posterior Maxilla with ObturatorSupported by Zygomatic Implants

Abstract: Prosthetic rehabilitation of atrophic maxilla and large maxillary defects can be done successfully by zygomatic implant-supported prosthesis. Zygomatic implants are an avant-garde to complex and invasive-free vascularised osteocutaneous flaps, distraction osteogenesis, and the solution to flap failures. A treated case of tuberculous osteomyelitis, with a class II (Aramany's classification) maxillary defect, reported to oral maxillofacial department, Government Dental College (RUHS-CODS). The defect in this gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…La capacidad masticatoria, retención, estabilidad, pronunciación de los pacientes mejoran sustancialmente. [9] El objetivo del informe clínico es restaurar estética, función, fonética en paciente geriátrico con patologías sistémicas preexistentes controladas aplicando protocolo de rehabilitación oral completa.…”
Section: Discussionunclassified
“…La capacidad masticatoria, retención, estabilidad, pronunciación de los pacientes mejoran sustancialmente. [9] El objetivo del informe clínico es restaurar estética, función, fonética en paciente geriátrico con patologías sistémicas preexistentes controladas aplicando protocolo de rehabilitación oral completa.…”
Section: Discussionunclassified
“…In the present case, since the hard palate was sectioned, the prosthetic rehabilitation was planned with an obturator supported by a zygomatic implant considering the age of the patient. The major advantage of these implants is that they eliminate the use of graft material and its associated infections [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mittal et al suggested the use of single-piece zygomatic implants to provide retention and support for an acrylic resin obturator and to alleviate osteocutaneous grafting procedure in a large maxillary defect. 42 Limitations associated with zygomatic implants include unavailability of bone, restricted intra-operative vision, anatomic complexity and variability of zygoma bone. 43 Also, overloading leverage in large defects, overgrowth of local soft tissue preventing abutment connection, sinus infections, facial pain, damage to surrounding structures and positional errors can adversely affect the success rate.…”
Section: Conventional Definitive Obturatormentioning
confidence: 99%